Engineering a halloysite nanotube-enhanced hydrogel 3D skin model for modulated inflammation and accelerated wound healing - Rui Xu; Xihong Fu; Lerong Lun; Wenjing Jiang; Xuemei Situ; Xiaobao Huang; Ying Xiong; Chun Liu; Fang Wang (Bioactive Materials)
The medicine field continues to encounter obstacles in understanding the etiology of skin inflammation and the process of skin wound repair. Developing sustainable and effective three-dimensional (3D) skin models for investigating inflammatory skin biology remains a challenge. By incorporating halloysite nanotubes (HNT) into a composite collagen/alginate/hyaluronic acid hydrogel, we created a novel 3D skin model and introduced keratinocytes and fibroblast cells into it. We demonstrate that the modified 3D skin model is capable of enhancing the differentiation and adhesion behaviors of keratinocytes and fibroblast cells in vitro and promoting wound healing in vivo. These characteristics highlight the potential of this approach for the study of skin inflammation, wound healing, regeneration, aging, and beyond.